Subspecies and Distribution. N. n. noctula Schreber, 1774 — throughout Europe from Great Britain, France, and Spain E to W Russia, W Kazakhstan, and SW Turkmenistan, including S Scandinavia, Gotland and Oland Is, and Cyprus (Cyprus records somewhat tentatively regarded as this subspecies). Absent throughout much of Iberia and is locally extinct in Portugal. N. n. lebanoticus D. L. Harrison, 1962 — WC & SW Syria, Lebanon, and NE Israel. N. n. mecklenburzevi Kuzyakin, 1934 — SC & E Kazakhstan, SC Russia, W Uzbekistan, Tajikistan, Kyrgyzstan, and NW China (Xinjiang). The species may be present in N Africa, with two records claimed from Algeria in 1858, but these may represent N. lasiopterus; further sampling is needed. in Vespertilionidae - Don E. Wilson; Russell A. Mittermeier (Lynx Edicions, 2019)
Subspecies and Distribution. N. n. noctula Schreber, 1774 — throughout Europe from Great Britain, France, and Spain E to W Russia, W Kazakhstan, and SW Turkmenistan, including S Scandinavia, Gotland and Oland Is, and Cyprus (Cyprus records somewhat tentatively regarded as this subspecies). Absent throughout much of Iberia and is locally extinct in Portugal. N. n. lebanoticus D. L. Harrison, 1962 — WC & SW Syria, Lebanon, and NE Israel. N. n. mecklenburzevi Kuzyakin, 1934 — SC & E Kazakhstan, SC Russia, W Uzbekistan, Tajikistan, Kyrgyzstan, and NW China (Xinjiang). The species may be present in N Africa, with two records claimed from Algeria in 1858, but these may represent N. lasiopterus; further sampling is needed. Published as part of Don E. Wilson & Russell A. Mittermeier, 2019, Vespertilionidae, pp. 716-981 in Handbook of the Mammals of the World – Volume 9 Bats, Barcelona :Lynx Edicions on page 766, DOI: 10.5281/zenodo.6397752